1999
DOI: 10.1037/0022-0663.91.2.273
|View full text |Cite
|
Sign up to set email alerts
|

The effects of story structure on the recall of stories in children with attention deficit hyperactivity disorder.

Abstract: This study explored influences of story structure properties on recall of story events by children with and without attention deficit hyperactivity disorder (ADHD). Participants listened to and retold 2 stories. Two properties of the stories' causal structure were derived: the number of causal connections an event has to other events and whether an event is on the causal chain linking events from beginning to end. The extent to which causal properties and the more subjective property of perceived importance pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 44 publications
8
73
0
6
Order By: Relevance
“…Lorch, O'Neil et al (2004) replicated these results using aurally presented narratives. These studies, like Lorch, Sanchez et al (1999), found that children with ADHD benefited less from causal structure than the comparison group.…”
Section: Attention and Causal Understandingmentioning
confidence: 99%
See 4 more Smart Citations
“…Lorch, O'Neil et al (2004) replicated these results using aurally presented narratives. These studies, like Lorch, Sanchez et al (1999), found that children with ADHD benefited less from causal structure than the comparison group.…”
Section: Attention and Causal Understandingmentioning
confidence: 99%
“…Children with attentional deficits can perform at typical levels when they can allocate their attention similarly to comparison children. Studies by Lorch and colleagues (Lorch, Eastham et al, 2004;Renz et al, 2003;Lorch et al, 2000;Lorch, Diener et al, 1999;Lorch, Sanchez et al, 1999) suggest that attention skills are important for causal understanding across a range of ages.…”
Section: Attention and Causal Understandingmentioning
confidence: 99%
See 3 more Smart Citations